Porous ferric fluoride, preparation method and application of porous ferric fluoride in lithium ion battery

Porous iron fluoride was prepared by Lewis acid-base reaction, which solved the problems of capacity and energy density limitations and high preparation risks of traditional cathode materials. It enabled large-scale production with high capacity, high energy density and safety, and is suitable for lithium-ion battery cathodes.

CN121672591APending Publication Date: 2026-03-17JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610203656.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-12
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Traditional cathode materials have capacity and energy density close to the theoretical upper limit, metal mineral resources are scarce, and existing methods for preparing iron fluoride are cumbersome and dangerous, making large-scale synthesis difficult.

Method used

Porous iron fluoride was prepared by Lewis acid-base reaction. Through stirring, precipitation, washing, drying and heat treatment, iron fluoride with a porous structure was prepared and then mixed with conductive agent and binder for use as the positive electrode of lithium-ion battery.

Benefits of technology

It achieves high capacity and high energy density, simplifies the preparation process, avoids the use of hazardous chemicals, is suitable for large-scale production, improves electrolyte wetting and electrical contact, and enhances electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672591A_ABST
    Figure CN121672591A_ABST
Patent Text Reader

Abstract

The invention discloses porous ferric fluoride, a preparation method and application of the porous ferric fluoride in a lithium ion battery, and belongs to the technical field of lithium ion batteries. The method comprises the following steps: stirring Lewis alkali and iron-containing Lewis acid under a heating condition to form a clear solution, adding a carbon source into the clear solution, and stirring to form uniform slurry; adding ammonium bifluoride, continuously stirring, alternately washing the obtained precipitate with ethanol and acetone, centrifuging until the supernatant is colorless and transparent, and drying to obtain a precursor; and finally, uniformly grinding the precursor, performing heat treatment, naturally cooling to room temperature, and fully grinding to obtain the porous ferric fluoride. The preparation process is simple and safe, the cost is low, the use of dangerous chemicals hydrofluoric acid and nitrogen fluoride is avoided, and large-scale synthesis can be realized; the prepared ferric fluoride has a porous morphology, is beneficial to electrolyte infiltration, ensures that the electrical contact between active particles is not influenced while the active material is in full contact with the electrolyte, and improves the electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of lithium ion batteries, and particularly relates to a porous iron fluoride, a preparation method and application thereof in lithium ion batteries. BACKGROUND

[0002] With the rapid development of new energy vehicles, portable electronic devices and large-scale energy storage power stations, people's requirements for secondary batteries are getting higher and higher. The rapid emergence of advanced negative electrode materials also makes the positive electrode material become the key factor hindering the capacity and energy density of lithium ion batteries. Traditional intercalation type positive electrode materials, such as lithium iron phosphate and lithium cobaltate, are based on single electron transfer, and the capacity and energy density have reached the theoretical limit, which is difficult to meet the increasing demand of people. Moreover, the metal minerals required in the traditional positive electrode materials, such as cobalt, have low abundance on the earth, which also makes its price continue to grow. Therefore, there is an urgent need for new positive electrode materials with high specific capacity and high energy density.

[0003] Metal fluorides have the advantages of sustainable production, safety, environmental protection and high energy density, and are suitable for the next generation of lithium ion batteries. Among them, iron fluoride based on three-electron transfer mechanism has a high theoretical capacity of 712 mAh / g and a high energy density of 1947 Wh / kg. At the same time, the earth's iron resources are abundant, so iron fluoride has very high cost-effectiveness and is environmentally friendly. However, iron fluoride itself has serious defects, such as low electronic conductivity and large volume expansion, which seriously hinder its development. The reported preparation methods of iron fluoride are mostly complicated processes, which need to go through several intermediate products to obtain iron fluoride, which is difficult to synthesize on a large scale; or need to use dangerous chemicals such as hydrofluoric acid and nitrogen fluoride for fluorination, which greatly increases the danger of preparing the material. SUMMARY

[0004] In view of the above problems, the present application aims to provide a porous iron fluoride prepared based on Lewis acid-base reaction, a preparation method and application thereof in lithium ion batteries.

[0005] One of the purposes of the present application is to provide a preparation method of porous iron fluoride, the steps of which are as follows:

[0006] (1) Stirring Lewis base and iron-containing Lewis acid under heating conditions to form a clear solution;

[0007] (2) Adding a carbon source to the clear solution obtained in step (1) and stirring at 50-70℃ to form a uniform slurry; then adding ammonium hydrogen fluoride and continuing to stir for 11-13h to obtain a precipitate;

[0008] (3) Washing the precipitate obtained in step (2) with ethanol and acetone alternately, and centrifuging until the supernatant is colorless and transparent, and then drying to obtain a precursor;

[0009] (4) grinding the precursor obtained in step (3) uniformly, and then performing heat treatment, and after naturally cooling to room temperature, grinding again to obtain porous ferric fluoride.

[0010] Preferably, the iron-containing Lewis acid in step (1) is at least one of ferric nitrate nonahydrate, anhydrous ferric chloride, and ferric sulfate hydrate;

[0011] Preferably, the Lewis base in step (1) is at least one of sulfolane and aminosulfonyl;

[0012] Preferably, the molar ratio of the iron-containing Lewis acid to the Lewis base in step (1) is 1:1-4;

[0013] Preferably, the heating temperature in step (1) is 30-70℃;

[0014] Preferably, the carbon source in step (2) is at least one of carbon nanotubes and Ketjen black;

[0015] Preferably, the molar ratio of Fe ions in the iron-containing Lewis acid to F ions in ammonium fluoride is 1:3-6;

[0016] Preferably, the mass amount of the carbon source in step (2) accounts for 0-17% of the final product porous ferric fluoride; when no carbon source is added, the final product is porous FeF3, and when a carbon source is added, the final product is porous FeF3@C composite material; the ferric fluoride has a porous morphology with irregular geometric shape;

[0017] Preferably, the drying in step (3) is vacuum drying at 40-80℃;

[0018] Preferably, the heat treatment in step (4) is pre-sintering at 100-200℃ for 4-6h, and then sintering at 200-300℃ for 4-6h in an air, nitrogen or argon atmosphere.

[0019] The second object of the present application is to provide a porous ferric fluoride prepared by the above preparation method.

[0020] The third object of the present application is to provide the application of the above porous ferric fluoride in lithium ion batteries, which is to mix the prepared porous ferric fluoride with a conductive agent and a binder, grind them uniformly, add N-methyl pyrrolidone (NMP) to grind them into a uniform slurry, uniformly coat the slurry on an aluminum foil current collector, and after drying, use it as a lithium ion battery positive electrode to assemble a lithium ion half battery or a lithium ion soft pack battery with metal lithium and an organic electrolyte.

[0021] The beneficial effects of the present application are as follows:

[0022] (1) The preparation of porous iron fluoride based on Lewis acid-base reaction of the present invention is simple, safe and low cost, avoids the use of dangerous chemicals hydrofluoric acid and nitrogen fluoride, and the preparation method of the present invention can be synthesized on a large scale.

[0023] (2) The iron fluoride prepared by the Lewis acid-base reaction of the present invention has a porous morphology. The porous structure is conducive to electrolyte wetting, ensuring that the active material and the electrolyte are in full contact without affecting the electrical contact between the active particles, thereby improving the electrochemical performance.

[0024] (3) The prepared porous iron fluoride was tested for its electrochemical performance in lithium-ion batteries. The experimental results showed that the prepared porous iron fluoride could achieve high capacity and high energy density and could be used to assemble soft-pack batteries. Attached Figure Description

[0025] Figure 1 The images show the XRD patterns of the FeF3@C prepared in Example 1 and the FeF3 materials prepared in Example 2 of this invention.

[0026] Figure 2 SEM images of the FeF3@C prepared in Example 1 and the FeF3 material prepared in Example 2 of this invention;

[0027] Figure 3 This is a graph showing the charge-discharge performance of a lithium-ion half-cell assembled with FeF3@C material as the positive electrode in Example 3 of the present invention at a current density of 50 mA / g.

[0028] Figure 4 The cycling performance curve of the lithium-ion half-cell assembled with FeF3@C material as the positive electrode in Example 3 of the present invention at a current density of 1000 mA / g is shown.

[0029] Figure 5 The rate performance curve of the lithium-ion half-cell assembled with FeF3@C material as the positive electrode in Example 3 is shown.

[0030] Figure 6 This is the cycle performance curve of the soft-pack battery assembled with FeF3@C material as the positive electrode in Example 4 of the present invention at a current density of 100 mA / g;

[0031] Figure 7 The images show the XRD patterns of the FeF3@C-10 and FeF3@C-50 materials prepared in Example 5 of this invention.

[0032] Figure 8 The graphs show the charge-discharge performance of lithium-ion half-cells assembled with FeF3@C-10 and FeF3@C-50 materials as positive electrodes in Example 5 of the present invention at a current density of 50 mA / g. Detailed Implementation

[0033] Example 1: Preparation of porous FeF3@C

[0034] (1) Stir 0.01 mol sulfolane and 0.005 mol ferric nitrate nonahydrate (the molar ratio of iron-containing Lewis acid to Lewis base is 1:2) at 60 °C until a clear solution is formed;

[0035] (2) Add 20 mg of Ketjen black (the amount of carbon source is 5.03% of the final product) to the clear solution obtained in step (1) and stir at 60°C until a uniform slurry is formed. Then add 0.0075 mol of ammonium bifluoride and continue stirring for 12 hours. The molar ratio of Fe ions in the iron-containing Lewis acid to F ions in the ammonium bifluoride is 1:3.

[0036] (3) Wash the precipitate obtained in step (2) with ethanol and acetone alternately, centrifuge at 8000 rpm for 6 minutes until the supernatant is colorless and transparent, and then vacuum dry at 60°C to obtain the precursor.

[0037] (4) After grinding the precursor obtained in step (3) evenly, it is pre-sintered at 150°C for 5 hours in air atmosphere, then sintered at 250°C for 5 hours. After naturally cooling to room temperature, it is fully ground and the powder is collected to obtain 0.65g of FeF3@C.

[0038] Depend on Figure 1 As can be seen, the XRD pattern of the FeF3@C material in Example 1 shows that all diffraction peaks of the synthesized material point to FeF3(H2O) of PDF #04-009-0959. 0.33 The sample has good crystallinity and no other impurities. Figure 2 (a) in the image is a SEM image of FeF3@C, derived from... Figure 2 As can be seen from (a) in Example 1, the FeF3@C sample has an irregular porous morphology.

[0039] Example 2: Preparation of porous FeF3

[0040] The preparation method of this embodiment is basically the same as that of Example 1. The difference is that the step of adding carbon source in step (2) is omitted, and ammonium fluoride is added directly after obtaining the clear solution in step (1). The amount of raw materials and subsequent steps are the same as those in Example 1.

[0041] Depend on Figure 1 As can be seen, the XRD pattern of the FeF3 material in Example 2 shows that all diffraction peaks of the synthesized material point to FeF3(H2O) of PDF #04-009-0959. 0.33 The sample has good crystallinity and no other impurities. Figure 2 Image (b) is a SEM image of FeF3, derived from...Figure 2 (b) It can be seen that the FeF3 sample in Example 2 has an irregular porous morphology.

[0042] The SEM images from Examples 1 and 2 clearly demonstrate that the method described in this invention can easily and quickly prepare iron fluoride with a porous structure. The porous structure ensures close electrical contact between the conductive carbon and the active particles, and also promotes sufficient wetting of the electrolyte and rapid transport of lithium ions. The abundant pore structure can effectively buffer the significant volumetric strain generated during the conversion reaction, thereby improving the cycling stability of the electrode.

[0043] Example 3: Preparation of lithium-ion battery cathode, battery assembly and testing

[0044] (1) Preparation of the positive electrode: FeF3@C obtained in Example 1 was used as the positive electrode material and mixed with conductive carbon black (Super-P) as a conductive agent and polyvinylidene fluoride (PVDF) as a binder at a mass ratio of 7:2:1 (49mg:14mg:7mg). The mixture was then ground thoroughly until homogeneous, and 0.5mL of N-methylpyrrolidone (NMP) was added dropwise. The mixture was then ground until a homogeneous slurry was formed. This slurry was then coated onto a clean aluminum foil current collector and dried in a vacuum drying oven at 60°C (the thickness of the positive electrode material on the aluminum foil current collector was 400μm). After drying, the aluminum foil loaded with the material was cut into circular pieces with a diameter of 10mm to serve as the positive electrode of the battery.

[0045] (2) Preparation of electrolyte: In an argon glove box with water and oxygen content not exceeding 0.1 ppm, 1.877 g of lithium bis(fluorosulfonyl)imide (LiFSI) was added to 8.67 g of ethylene glycol dimethyl ether (DME), and stirred at room temperature until LiFSI was completely dissolved to obtain electrolyte 1M LiFSI / DME.

[0046] (3) Battery assembly: In an argon glove box with water and oxygen content not exceeding 0.1 ppm, assemble lithium-ion half-cells. The battery case is CR2032 type, the positive electrode is the positive electrode of the battery prepared above, the negative electrode is a lithium metal disc, the electrolyte is 1M LiFSI / DME, and the separator is Celgard 2325.

[0047] The lithium-ion half-cell assembled in Example 3 was left to stand at room temperature for 8 hours before electrochemical performance testing was performed, as in Examples 1-3.

[0048] Test Example 1: Low Current Charge and Discharge Test

[0049] At room temperature, the assembled lithium-ion half-cell of Example 3 was subjected to low-current charge-discharge tests: the electrochemical performance of the battery was tested using the Wuhan Landian Battery Testing System, with a test current density of 50 mA / g and a voltage range of 1~4V. The charge-discharge curves of the battery for the first 5 cycles are shown below.Figure 3 As shown in (a) in the figure, the horizontal axis represents the discharge specific capacity and the vertical axis represents the voltage. Figure 3 (a) in the graph shows the charge-discharge curves for the first 5 cycles. Figure 3 (b) is the cycle performance curve; according to Figure 3 As can be seen from (a) above, the battery exhibits a high discharge specific capacity of 759 mAh / g in the first cycle. The cycle performance at this current is as follows: Figure 3 As shown in (b) above, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis represents the coulombic efficiency. According to Figure 3 As can be seen from (b) in the figure, at a current density of 50 mA / g, after 100 cycles, the discharge specific capacity is 347 mAh / g and the coulombic efficiency remains at 100%.

[0050] Test Example 2: High Current Charge and Discharge Test

[0051] At room temperature, the lithium-ion half-cell assembled in Example 3 was subjected to high-current charge-discharge tests. The electrochemical performance of the battery was tested using the Wuhan Landian Battery Testing System. The battery test current density was 1000 mA / g, and the voltage range was 1~4V. The battery cycle performance was as follows: Figure 4 As shown, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis represents the coulombic efficiency. According to... Figure 4 It can be seen that even under high current, the battery still has a high discharge specific capacity. After 100 cycles, the discharge specific capacity is 232.3 mAh / g, and the coulombic efficiency remains at 100%.

[0052] Test Example 3: Rate Performance Test

[0053] The rate performance of the lithium-ion half-cell assembled in Example 3 was tested at room temperature. The electrochemical performance of the battery was tested using the Wuhan Landian Battery Testing System. The battery test current densities were sequentially set to 50 mA / g, 100 mA / g, 200 mA / g, 300 mA / g, 500 mA / g, 1000 mA / g, and 2000 mA / g, then returned to 50 mA / g. Each current density was cycled 10 times, with a voltage range of 1–4 V. The battery rate performance was as follows: Figure 5 As shown, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis represents the coulombic efficiency. According to... Figure 5 It can be seen that the average discharge specific capacity of the battery under different current densities is 492.5, 445.3, 401.4, 369.7, 317.8, 238.8, and 151.0 mAh / g, respectively.

[0054] Example 4: Assembly and Testing of Lithium-ion Pouch Cells

[0055] (1) Preparation of the positive electrode: FeF3@C obtained in Example 1 was used as the positive electrode material and mixed with Super-P and PVDF at a mass ratio of 7:2:1 (35mg:10mg:5mg). The mixture was then ground thoroughly until homogeneous, and 0.36mL of N-methylpyrrolidone (NMP) was added dropwise. The mixture was then ground until a homogeneous slurry was formed. The slurry was then coated onto a clean aluminum foil current collector and dried in a vacuum drying oven at 60°C (the thickness of the positive electrode material on the aluminum foil current collector was 550μm). After drying, the aluminum foil loaded with the material was cut into a rectangle of 30mm×40mm to serve as the positive electrode of the battery.

[0056] (2) Assembly of soft-pack batteries: In an argon glove box with water and oxygen content not exceeding 0.1 ppm, soft-pack batteries are assembled. The positive electrode is the positive electrode of the battery prepared above, the negative electrode is lithium metal strip, the electrolyte is 1M LiFSI / DME, and the separator is Celgard2325.

[0057] (3) Testing of the pouch battery: The pouch battery assembled in Example 4 was subjected to charge-discharge tests at room temperature. The electrochemical performance of the battery was tested using the Wuhan Landian Battery Testing System. The battery test current density was 100 mA / g, and the voltage range was 1~4V. The battery cycle performance was as follows: Figure 6 As shown, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis represents the coulombic efficiency. According to... Figure 6 It can be seen that the soft-pack battery can achieve a discharge specific capacity of 386.26 mA / g at a current density of 100 mA / g, and the discharge capacity of the positive electrode exceeds 10 mAh. It can be stably cycled 100 times, which proves that the iron fluoride positive electrode of the present invention has the potential for commercial application.

[0058] Example 5: Large-scale preparation of porous FeF3@C and its application in lithium-ion batteries

[0059] (1) Material Preparation: The preparation method in this embodiment is basically the same as that in Example 1, except that the amounts of all raw materials, namely sulfolane, ferric nitrate nonahydrate, Ketjen black, and ammonium bifluoride, are increased by 10 times in equal proportions to obtain FeF3@C-10; and increased by 50 times to obtain FeF3@C-50. Figure 7 As can be seen, the XRD patterns of FeF3@C-10 and FeF3@C-50 materials in Example 5 show that all diffraction peaks of the synthesized materials point to FeF3(H2O) of PDF #04-009-0959. 0.33 The sample has good crystallinity and no other impurities.

[0060] (2) Assembly of lithium-ion half-cells: Using FeF3@C-10 and FeF3@C-50 as active materials, the positive electrode of the battery, electrolyte and battery were prepared and assembled according to the steps of Example 3;

[0061] (3) Testing of the lithium-ion half-cell: The assembled lithium-ion half-cell of Example 5 was subjected to charge-discharge tests in the Wuhan Landian Battery Testing System. The battery test current density was 50 mA / g, and the voltage range was 1~4V. The charge-discharge curves of the battery in the first 5 cycles are shown below. Figure 8 As shown, the horizontal axis represents the discharge specific capacity, and the vertical axis represents the voltage. Figure 8 (a) shows the charge-discharge curves of FeF3@C-10 for the first 5 cycles. Figure 8 (b) shows the charge-discharge curves of FeF3@C-50 for the first 5 cycles. According to... Figure 8 As can be seen from (a) in the figure, when the raw materials are increased proportionally by 10 times, the battery has a high discharge specific capacity exceeding 550 mAh / g. According to Figure 8 As can be seen from (b), even with the raw materials increased proportionally by 50 times, the battery discharge specific capacity can still exceed 490 mAh / g. Therefore, the preparation method of this invention can be used for large-scale synthesis and has great commercial potential.

[0062] Finally, it should be noted that the above description is for illustrative purposes only and is not intended to limit the invention. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of this invention, as long as they do not depart from the spirit and scope of the technical solutions of this invention, should be covered within the scope of the claims of this invention.

Claims

1. A method for producing porous iron fluoride, characterized by: The steps are as follows, (1) stirring the Lewis base and the iron-containing Lewis acid under heating conditions until a clear solution is formed; (2) adding a carbon source to the clear solution obtained in step (1) and stirring at 50-70°C until a uniform slurry is formed; then adding ammonium hydrogen fluoride and continuing to stir for 11-13 h to obtain a precipitate; (3) washing the precipitate obtained in step (2) with ethanol and acetone alternately, then centrifuging until the supernatant is colorless and transparent, and drying to obtain a precursor; (4) grinding the precursor obtained in step (3) uniformly, then heat treating, naturally cooling to room temperature, and then thoroughly grinding to obtain porous iron fluoride.

2. The method for preparing porous iron fluoride as described in claim 1, characterized in that: The iron-containing Lewis acid in step (1) is at least one of ferric nitrate nonahydrate, anhydrous ferric chloride, and ferric sulfate hydrate, and the Lewis base is at least one of sulfolane and aminosulfone.

3. The method for preparing porous iron fluoride as described in claim 1, characterized in that: The molar ratio of the amount of the iron-containing Lewis acid to the amount of the Lewis base in step (1) is 1:1-4, and the heating temperature is 30-70°C.

4. The method for preparing porous iron fluoride as described in claim 1, characterized in that: The carbon source in step (2) is at least one of carbon nanotubes and Ketjen black.

5. The method for preparing porous iron fluoride as described in claim 1, characterized in that: The molar ratio of the amount of Fe ions in the iron-containing Lewis acid to the amount of F ions in ammonium hydrogen fluoride is 1:3-6, and the mass amount of the carbon source accounts for 0-17% of the final product, porous iron fluoride.

6. The method for preparing porous iron fluoride as described in claim 1, characterized in that: The drying in step (3) is vacuum drying at 40-80°C.

7. The method for preparing porous iron fluoride as described in claim 1, characterized in that: The heat treatment in step (4) is pre-sintering at 100-200°C for 4-6 h, and then sintering at 200-300°C for 4-6 h in an atmosphere of air, nitrogen, or argon.

8. A porous iron fluoride characterized by: The porous iron fluoride is prepared by the preparation method of any one of claims 1-7.

9. The use of the porous iron fluoride of claim 8 in a lithium ion battery.

10. Use of a porous iron fluoride in a lithium-ion battery according to claim 9, characterized in that: The porous iron fluoride is mixed with a conductive agent and a binder, thoroughly ground to be uniform, then N-methyl pyrrolidone is added and ground to form a uniform slurry, the slurry is uniformly applied to an aluminum foil current collector, and after drying, it is used as a lithium ion battery anode to assemble a lithium ion half battery or a lithium ion soft pack battery with metal lithium and an organic electrolyte.

Citation Information

Patent Citations

  • Deep eutectic solvent, metal fluoride, lithium ion battery positive electrode material and preparation method thereof

    CN116936754A

  • In-situ preparation and application of solid polymer electrolyte

    WO2023109659A1